Ultrafast Wiggling and Jiggling: Ir2(1,8-diisocyanomenthane)42 - Pižl, Martin; Hunter, Bryan M; Greetham, Gregory M; Towrie, Michael; Záliš, Stanislav; Gray, Harry B; Vlček, Antonín (The journal of physical chemistry. A, 2017)
Binuclear complexes of d8 metals (PtII, IrI, RhI,) exhibit diverse photonic behavior, including dual emission from relatively long-lived singlet and triplet excited states, as well as photochemical energy, electron, and atom transfer. Time-resolved optical spectroscopic and X-ray studies have revealed the behavior of the dimetallic core, confirming that M-M bonding is strengthened upon dσ* → pσ excitation. We report the bridging ligand dynamics of Ir2(1,8-diisocyanomenthane)42+ (Ir(dimen)), investigated by fs-ns time-resolved IR spectroscopy (TRIR) in the region of C≡N stretching vibrations, ν(C≡N), 2000-2300 cm-1. The ν(C≡N) IR band of the singlet and triplet dσ*pσ excited states is shifted by -22 and -16 cm-1 relative to the ground state due to delocalization of the pσ LUMO over the bridging ligands. Ultrafast relaxation dynamics of the 1dσ*pσ state depend on the initially excited Franck-Condon molecular geometry, whereby the same relaxed singlet excited state is populated by two different pathways depending on the starting point at the excited-state potential energy surface. Exciting the long/eclipsed isomer triggers two-stage structural relaxation: 0.5 ps large-scale Ir-Ir contraction and 5 ps Ir-Ir contraction/intramolecular rotation. Exciting the short/twisted isomer induces a ∼5 ps bond shortening combined with vibrational cooling. Intersystem crossing (70 ps) follows, populating a 3dσ*pσ state that lives for hundreds of nanoseconds. During the first 2 ps, the ν(C≡N) IR bandwidth oscillates with the frequency of the ν(Ir-Ir) wave packet, ca. 80 cm-1, indicating that the dephasing time of the high-frequency (16 fs)-1 C≡N stretch responds to much slower (∼400 fs)-1 Ir-Ir coherent oscillations. We conclude that the bonding and dynamics of bridging di-isocyanide ligands are coupled to the dynamics of the metal-metal unit and that the coherent Ir-Ir motion induced by ultrafast excitation drives vibrational dephasing processes over the entire binuclear cation.